Towards a new stakeholder-inclusive conceptual framework to strengthen internal corporate image (Communicare: Journal for Communication Studies in Africa, 2022)
It is widely reported in the literature that employees’ image of the organisation has a direct influenceon external stakeholders’ image of the organisation. This research attempted to address theneed for an approach that facilitates employee engagement coupled with a leadership approachthat allows collaboration, inclusion and co-operation within the organisation, to strengthenthe internal corporate image. A synthesis of the literature from a unique stakeholder-inclusiveperspective, depicted in the King III Report on corporate governance, was conducted to identifythe theoretical principles for a preliminary conceptual framework explored through a case studyapproach. Parsec Technologies Pty Ltd was purposively selected as case study, because it wasthe 2012 and 2013 winner in the manufacturing sector of the Deloitte Best Company to Work For(BCTWF) survey, and served as a best practice organisation in the context of this research. Datatriangulation by means of one-on-one interviews, focus groups and an open-ended survey wasconducted with employees to determine the pragmatic relevance of the proposed framework. Thefindings culminated in a new generic stakeholder-inclusive conceptual framework to strengthenthe internal corporate image by means of the AA1000 Stakeholder Engagement Standardelements and responsible leadership. Although a single case study is limited, this frameworkcontributed to the body of knowledge on corporate image to provide organisations with guidelinesfor strengthening their internal corporate image.